Experimental study of the state-of-the-art offshore system integrating a floating offshore wind turbine with a steel fish farming cage. (November 2021) - Lei, Yu; Zheng, Xiang Yuan; Li, Wei; Zheng, Huadong; Zhang, Qi; Zhao, Shengxiao; Cai, Xiao; Ci, Xiang; He, Qinxuan
Abstract: An innovative offshore system integrating a floating offshore wind turbine with a steel fish farming cage (FOWT-SFFC) has recently been developed by the two leading authors for offshore wind and aquaculture industry. The purpose of this paper is to investigate the dynamic responses of FOWT-SFFC subjected to simultaneous wind and wave actions in the harsh South China Sea environment by a series of model tests. The tests are conducted at the Tsinghua Ocean Engineering Basin with Froude scale of 1:30. In this paper, the similarity law and setup of model tests are given first. Then a series of calibration tests and identification tests are carried out to validate the capacity of wind generator and wave maker, and to identify the vibration frequencies of tower, the stiffness of mooring system, natural periods and system damping, motion response amplitude operators (RAOs) of FOWT-SFFC, and thrust-speed performance of the turbine in wave basin. After that, seakeeping tests are implemented for random waves, followed by a sequence of load cases including normal operating and extreme conditions. Constant wind speeds and random wind speeds are respectively considered in load combinations. The experimental results affirm the excellent seakeeping and dynamic performance of FOWT-SFFC. Existence of metal fish nets increases the damping of foundation's 6 degree-of-freedoms motions. Generally, the influence of nets on the dynamic responses is insignificant in wind sea states. Highlights: Dynamic responses of the new conceptual wind-aquaculture floater FOWT-SFFC are investigated through 1:30 model tests. It is the first time that random wind action on an offshore structure is considered in model tests. Nets effects on hydrodynamic damping and seakeeping performance of FOWT-SFFC are examined. The excellent dynamic performance is affirmed in terms of measured responses at tower and cage foundation.